الاستثناء الذي يعقب الجمل المعطوفة وأثر الخلاف فيه في اختلاف الفقهاء (The Role of Exception following Conjunction Sentences and its Effect on the Juristic Differences ) - محمد بن راشد الغاربي; المجاهد محمد سعيد خليل (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
يهدف البحث إلى بيان حكم الاستثناء الذي يعقب الجمل المعطوفة، فجاء البحث ليجيب على الأسئلة الآتية: ما معنى الاستثناء؟ وأين يقع محل النزاع بين العلماء في عودة الاستثناء الذي يعقب جملًا متوالية؟ وما هي أهم التطبيقات التي تنبني على هذا الخلاف؟ ولقد جعلناه مؤلفًا من مطلبين، الأول: في الاستثناء معناه وحكمه بعد الجمل المتعاطفة، والثاني: في مسائل تطبيقية على قاعدة الاستثناء الذي يعقب الجمل المعطوفة. أما المطلب الأول فأتحدث فيه عن معنى الاستثناء، ثم تحرير محل النزاع بين العلماء في عودة الاستثناء الذي يعقب جملًا متوالية، ولا بد أن نذكر أقوال العلماء في الاستثناء الذي يعقب جملًا معطوفة بالواو ونحوها من حروف العطف، ثم نقف على أدلة العلماء لنتمكن من الترجيح، ويأتي في الأخير دور مناقشة الأدلة. وأما القسم الثاني فلقد ذكرنا فيه التطبيقات، وتكلمنا عن اثنين منها، وقع فيها الخلاف بين العلماء في المستثنى والجمل المعطوفة. الكلمات المفتاحية: الاستثناء، الجمل المتعاطفة، الخلاف، الفقهاء. Abstract The purpose of the current study is to discuss and explain the issue of linguistic exceptions that follow conjunctive sentences. In this regard, the study attempts to answer the following questions: What does linguistic exception mean? What is the dispute among scholars in considering the exception that follows successive sentences? What are the most common effects that are based on this dispute? The study consists of two sections: First, the meaning of exception that follows conjunctive sentences. Second, the applied jurisprudential issues based on the linguistic exceptions that follow conjunctive sentences. The first section sheds light on the meaning of exception and then resolves the dispute among scholars in relating to exceptions that follow conjunctive sentences to all sentences or to the subsequent sentence. It is necessary to mention scholars’ opinions on the exceptions that follows conjunctive sentences by the conjunctive “and” or any other conjunctions. In addition, the paper focuses on comparing and evaluating the arguments of these scholars. The second section mentions two applied cases in which the dispute among scholars occurs with regard to exceptions and conjunctive sentences. Keywords: Exception, Conjunction, Disagreement, Jurists.